S-enriched porous polymer derived N-doped porous carbons for electrochemical energy storage and conversion - Zhang, Chao; Lu, Chenbao; Bi, Shuai; Hou, Yang; Zhang, Fan; Cai, Ming; He, Yafei; Paasch, Silvia; Feng, Xinliang; Brunner, Eike; Zhuang, Xiaodong (Frontiers of Chemical Science and Engineering, 2018)
Porous polymers have been recently recognized as one of the most important precursors for fabrication of heteroatom-doped porous carbons due to the intrinsic porous structure, easy available heteroatom-containing monomers and versatile polymerization methods. However, the heteroatom elements in as-produced porous carbons are quite relied on monomers. So far, the manipulating of heteroatom in porous polymer derived porous carbons are still very rare and challenge. In this work, a sulfur-enriched porous polymer, which was prepared from a diacetylene-linked porous polymer, was used as precursor to prepare S-doped and/or N-doped porous carbons under nitrogen and/or ammonia atmospheres. Remarkably, S content can sharply decrease from 36.3% to 0.05% after ammonia treatment. The N content and specific surface area of as-fabricated porous carbons can reach up to 1.32% and 1508 m2∙g–1, respectively. As the electrode materials for electrical double-layer capacitors, as-fabricated porous carbons exhibit high specific capacitance of up to 431.6 F∙g–1 at 5 mV∙s–1 and excellent cycling stability of 99.74% capacitance retention after 3000 cycles at 100 mV∙s–1. Furthermore, as the electrochemical catalysts for oxygen reduction reaction, as-fabricated porous carbons presented ultralow half-wave-potential of 0.78 V versus RHE. This work not only offers a new strategy for manipulating S and N doping features for the porous carbons derived from S-containing porous polymers, but also paves the way for the structureperformance interrelationship study of heteroatoms codoped porous carbon for energy applications. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-04-14
Keywords: porous carbons; porous polymers; sulfur and nitrogen doping; supercapacitor